Analisis Pelanggaran Prinsip Dasar Etika Akuntan pada PT. Timah Tbk. Tahun 2024 - Indah, Alika; Regina, Devanka; Aprillia , Mega; Raihanah, Syahla; Saridawati, Saridawati (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
The speed of information sharing in the digital era and technological advancements have transformed the way the accounting profession operates. In response to these developments, accountants are required to uphold high ethical standards to ensure the profession remains trusted by the public and stakeholders. This study aims to analyze violations of basic accounting ethics principles at PT. Timah Tbk., focusing on breaches of integrity, objectivity, competence, confidentiality, and professional behavior in financial reporting. Using a qualitative descriptive method, this research finds that PT. Timah Tbk. has manipulated financial statements, resulting in harm to stakeholders and diminishing public trust in the company. These ethical violations reflect dishonesty in financial reporting and breach the principle of objectivity, which requires accountants to act neutrally and impartially. The study also highlights the need for stricter enforcement of ethical codes within the accounting profession to maintain integrity and transparency in accounting practices.